The Theatrical Canvas : (The Symbiotic Relationship Between Theatre And Painting) - Dr. Lina M Kattan (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
Since ancient Greece, theatre has influenced the evolution of painting, shaping the techniques employed by painters in their works. This paper argues that the symbiotic relationship between distinct forms of expression—painting and theatre—has revolutionized art history. This relationship has blurred the boundaries between dynamic and static art while enriching the viewer’s aesthetic experience. The paper explores the history of art and visual culture and shows how this intertwined connection has impacted both. Painters were inspired by theatrical narrative scenes, set designs, costumes, and stage mood; consequently, they transformed how they arranged their compositions, techniques, and color choices. Artists tried to capture fleeting moments of performance by rearranging their figures and gestures, using storytelling elements, and charging them with symbolism. Furthermore, artists innovated new artistic techniques and color selections to depict more dynamic and psychologically intense, undeniably theatrical works. Through this new approach, painters successfully connected various art forms. Artists amplified the emotional and psychological resonance of painting, which fostered significant art movements and motivated numerous artists to employ uncommon tools and approaches in their work. All these initiatives established a continuous discourse between theatre and painting, stimulated creativity through interdisciplinarity, and established avenues for innovative future expressions.